2020
DOI: 10.1108/mf-07-2019-0322
|View full text |Cite
|
Sign up to set email alerts
|

Risk committee, corporate risk-taking and firm value

Abstract: PurposeThe authors empirically examine the impact of the stand-alone risk committee on corporate risk-taking and firm value.Design/methodology/approachThe authors argue that the existence of a stand-alone risk committee enhances the quality of corporate governance, which reduces corporate risk-taking and strengthens the firm value that might improve investor protection.FindingsThe authors find corporate risk-taking decline significantly for firms that have a stand-alone risk committee compared with firms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 63 publications
(106 reference statements)
7
20
0
1
Order By: Relevance
“…The risk committee is responsible for providing recommendations relating to optimal risk strategies as well as overseeing the “risk management framework” implementation. Some prior studies also found that a risk committee existence can reduce bank risk ( Aljughaiman and Salama, 2019 ; Bhuiyan et al., 2020 ). Therefore, we expect the risk committee to be able to enhance bank risk management effectiveness and propose the sixth hypothesis as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 91%
“…The risk committee is responsible for providing recommendations relating to optimal risk strategies as well as overseeing the “risk management framework” implementation. Some prior studies also found that a risk committee existence can reduce bank risk ( Aljughaiman and Salama, 2019 ; Bhuiyan et al., 2020 ). Therefore, we expect the risk committee to be able to enhance bank risk management effectiveness and propose the sixth hypothesis as follows:…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 91%
“…Jumreornvong et al (2019) concluded that increasing centralized ownership further reduces its risk-taking. Bhuiyan et al (2020) found that companies with an independent risk committee were less risktaking than companies with an audit and risk committee. Bucciol et al (2020) concluded a positive and significant relationship between emotional intelligence and risk-taking.…”
Section: The Relationship Between Narcissism Of Managers and Corporate Risk-takingmentioning
confidence: 99%
“…Komite risiko yang berdiri sendiri dan terpisah dari komite audit juga mampu meningkatkan tata kelola perusahaan yang baik. Dengan berkurangnya pengambilan risiko oleh manajemen perusahaan, kejahatan keuangan pun berkurang (Bhuiyan et al, 2020). Variabel komite risiko yang berdiri sendiri menggunakan variabel dummy dimana perusahaan dikategorikan menjadi dua yaitu ada atau tidaknya komite risiko yang berdiri sendiri.…”
Section: Komite Risiko Yang Berdiri Sendiriunclassified